An Aqueous Process for Durable Superamphiphobic Diblock Copolymer Coatings on Fabrics. Issue 8 (8th February 2016) - Zou, Hailiang; Lin, Shudong; Tu, Yuanyuan; Li, Fei; Hu, Jiwen; Liu, Guojun; Hu, Shengyu; Yang, Gonghua; Yu, Zhiwei
Abstract : Many strategies have been developed to prepare superamphiphobic fabrics that strongly repel water‐ and oil‐borne contaminants and etchants. However, the common drawback in these reported strategies is the use of organic solvents, which should be eliminated or reduced for practical applications. In this paper, the diblock copolymer of poly(2‐perfluorooctylethyl acrylate)‐block‐poly(glycidyl methacrylate‐ radom‐methoxy oligoethyleneglycolyl methacrylate) [PFOEA‐b‐P(GMA‐r‐mOEGMA)]is synthesized via atom transfer radical polymerization and used to coat cotton and poly(ethylene terphthalate) fabrics from an aqueous process. It is found that fabrics with tunable and robust wettablity can be prepared from copolymer solution at different concentrations. For example, fabrics coated at a copolymer solution concentration of 22.8 mg mL‐1 are superamphiphobic. This process of current stratey is environment‐friendly, simple, and reproducible, and may find commercial applications. Abstract : Functional diblock copolymers are prepared and used for the fabrication of durable superamphiphobic fabrics via an aqueous process.